2013
DOI: 10.1080/13607863.2013.819834
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and psychological symptoms of dementia and their management in care homes within the East of England: a postal survey

Abstract: This survey was a first attempt to estimate the use of antipsychotics in care homes. Despite measures to reduce antipsychotic use for all people with dementia in England, we found that 12% of care home residents were still prescribed antipsychotic medication. Around half of all care home managers reported they had experienced behaviours they found difficult. Antipsychotic medications and a variety of non-pharmacological interventions appear to be used concurrently in many care homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Table 2 shows the characteristics of the 4 case study care homes. Care staff on AM shift** 6 4/5 7 8/9 Care staff on PM shift** 6 4 7 7 Care staff on night shift** 2 2 4 4 *Information from a postal survey prior to the case studies [32] **Includes carers and nurses/seniors on shift, but excludes management, activity, maintenance, office and domestic staff The blurring between non-pharmacological interventions and activities Table 3 shows the wide variety of NPIs or activities which were found to be used in the four care homes. The observation data showed that activities were used in several ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the characteristics of the 4 case study care homes. Care staff on AM shift** 6 4/5 7 8/9 Care staff on PM shift** 6 4 7 7 Care staff on night shift** 2 2 4 4 *Information from a postal survey prior to the case studies [32] **Includes carers and nurses/seniors on shift, but excludes management, activity, maintenance, office and domestic staff The blurring between non-pharmacological interventions and activities Table 3 shows the wide variety of NPIs or activities which were found to be used in the four care homes. The observation data showed that activities were used in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a previous postal survey to care-home managers [32] were used to select suitable homes to target for the purposive sampling of the case studies. All eligible survey responses were analysed and sorted (n=291) and those homes most likely to be caring for people experiencing BPSD were selected as potential sites (n=80).…”
Section: Samplingmentioning
confidence: 99%
“…In the meta‐analysis by Sitzer, Twamley, and Jeste, it was stated that the effect size of cognitive training interventions was medium, patients gained cognitive and functional benefits, and cognitive training had positive effects on learning, memory, functionality, and daily activities . In another study on nonpharmacological implementations applied in nursing, houses in England were evaluated using a form developed by the researchers; therapies (64%) were commonly used among nonpharmacological practices applied for Alzheimer's and other types of dementia …”
Section: Introductionmentioning
confidence: 99%
“…6 In another study on nonpharmacological implementations applied in nursing, houses in England were evaluated using a form developed by the researchers; therapies (64%) were commonly used among nonpharmacological practices applied for Alzheimer's and other types of dementia. 7 Reminiscence group therapy is defined as vocal or silent recall of life events performed in the presence of a group. Reminiscence group therapy involves the discussion of past activities, events, and experiences, usually with the aid of tangible prompts.…”
mentioning
confidence: 99%
“…Whether these alternatives are tried before the use of antipsychotics is commenced is unclear. These alternatives could also be used simultaneously with antipsychotics to address severe challenging behaviour, especially as more complex cases need a multi‐level strategy …”
Section: Discussionmentioning
confidence: 99%